Gentle yet Manly: Xiao xian rou, Male Cosmetic Surgery and Neoliberal Consumer Culture in China. - Wen, Hua (Asian Studies Review, 2021)
This article explores the phenomenal growth in the popularity of the "little fresh meat" (xiao xian rou) androgynous, effeminate male beauty trend and the rise in the demand for male cosmetic surgery in the context of neoliberal consumer culture in China. This new male beauty trend is rooted in traditional Chinese gentle/benign wen masculinity, but it has also been influenced by the "flower boys" of South Korea and Japan and by Western metrosexuals. Drawing on men's accounts in Beauty Diaries posted on cosmetic surgery apps, the author argues that gentle wen and tough wu are not perceived dualistically by the men who opt for cosmetic surgery. Rather, "gentle yet manly" is a common narrative now invoked in the construction of masculinities. In a neoliberal consumer culture, men have more agency and freedom to engage in the beautification practices associated with femininity, but they are also constrained by hegemonic masculinity and must therefore negotiate with the dominant existing masculinity discourses to find their position in society. The resultant paradoxes in male identity associated with male cosmetic surgery reflect the fluidity and the unsettling nature of the constructions of hybrid masculinities in China.